Shared Governance: A Way to Improve the Care in an Inpatient Rehabilitation Facility. Issue 2 (March 2015) - Torres, Audrey; Kunishige, Nalani; Morimoto, Denise; Hanzawa, Tracie; Ebesu, Mike; Fernandez, John; Nohara, Lynne; SanAgustin, Eliseo; Borg, Stephanie
Abstract : Background: : Rehabilitation care is specialized and individualized requiring effective and efficient communication to achieve optimal patient outcomes. Purpose: : To examine how effective implementation of shared governance could improve care delivery, promote patient‐centered care, and improve patient outcomes. Design: : The shared governance approach included all members of the rehabilitation team (i.e., physical therapist, occupational therapist, speech therapist, registered nurse and nurse aide) and was implemented over 6 months. Findings/Conclusions: : The major end products of this shared governance effort were improved staff communication, problem solving, patient outcomes, and staff satisfaction on our stroke and brain injury unit. Clinical Relevance: : When effectively implemented and sustained, shared governance between all rehabilitation team stakeholders can increase the effectiveness of communication along with more positive patient and staff outcomes.